The legal framework for the user's right in social media platforms - Brakhas, Asos Namik (Journal of Legal and Political Studies, 2023)
In this research, we tried to put the user's right on social media platforms in a legal framework, by stating what is meant by social platforms for the purpose of distinguishing them from other electronic platforms, and shedding light on their most important elements. We also tried to explain the legal relationship that establishes between the user and the platform in the event of The user creates an electronic account on a specific platform, and adapts it, with the intention of clarifying the legal status of the user after creating the electronic account and the nature of the right that is generated from the user’s relationship with the platform, and we also determined the scope of the user’s right by presenting the controls of this right, whether the controls of the agreement or those imposed by the law, and presenting the penalties Approved for the user who exits using the platform from the controls set for him.
Keywords: social media platform; legal framework; legal status of the user,legal status; electronic account